Phytochemical Screening, Antioxidant Activity, GC–MS Analysis and Optimization Using Response Surface Methodology of Pimenta dioica (L.) Merr. Leaf Extracts - Vismaya, M. R.; Nevaditha, N. T. (Journal of Scientific Research, 2026)
This study investigates the antioxidant potential, phytochemical profile, and extraction optimization of Pimenta dioica (L.) Merr. leaves using Response Surface Methodology (RSM). Extractions were conducted with acetone, chloroform, methanol, petroleum ether, and water. Qualitative screening identified key phytochemicals, including terpenoids, flavonoids, phenols, alkaloids, and phytosterols, with methanol and aqueous extracts showing the highest content. Antioxidant assays revealed strong radical-scavenging activity, with the aqueous extract achieving 95.08 % inhibition of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and 70.23 % nitric Oxide (NO) scavenging at 0.5 mg/mL, comparable to ascorbic acid. GC–MS analysis identified bioactive compounds, including dodecanoic acid, 1-hexadecane sulfonic acid, oxalic acid ester, and 2-chloro-5-iodobenzamide, many of which exhibit antioxidant and anti-inflammatory properties. The Box–Behnken Design was used to optimize extraction variables: extract concentration, extraction time, and temperature. Optimal conditions were found to be 60.45 ºC, 499.99 µg/mL, and 6 hours, resulting in 93.4 % DPPH activity, 54.46 % NO scavenging, a Total Phenolic Content (TPC) of 156.45 mg GAE g⁻¹, and an extraction yield of 9.65 %, with an overall desirability of 0.995. The findings highlight L. as a promising natural source of antioxidants and bioactive compounds for pharmaceutical, nutraceutical, and food applications.